Pertumbuhan dan Uji Kualitatif Kandungan Metabolit Sekunder Kalus Gatang (Spilanthes acmella Murr.) dengan Penambahan PEG untuk Menginduksi Cekaman Kekeringan - - Zulhilmi; - Suwirmen; Netty W Surya (Jurnal Biologi Universitas Andalas, 2012)
The study about the growth and qualitative test of secondary metabolite content of the callus culture of Spilanthes acmella Murr. with addition of PEG to induce drought stress had been done used completely randomized design with six treatments and six replications. The treatments were the addition of PEG in various consentration : 1%, 2%, 3%, 4%, 5% and control (without addition of PEG). The result showed that the addition of PEG to medium could decrease fresh weight of callus. The fresh weight of callus was decrease significantly by addition 5% PEG. On the qualitative test of secondary metabolite, alkaloid content was increase by addition of 2% - 5% PEG (++), terpenoid content was increase by addition 3% - 4% PEG (++) and fenolik was found on 4% PEG (+).Keywords: callus culture, secondary metabolite, PEG, drought stress, Spilanthes acmella